Postpartum diseases and their effects on reproduction in dairy cows - J.F. Rocha; S.R.B. Couto; N.M.P.M. Caparelli; J.P.N. Andrade; C.G. Jayme; M.R.B. Mello (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT This study evaluated the effects of postpartum diseases and body condition score (BCS) on the reproductive performance of dairy herds. Cows were monitored during the postpartum to diagnose diseases and changes in BCS. The cows were divided into those with no disease and those with one or more diseases. The incidence of diseases, pregnancy rate (PR) at the first postpartum service, number of days open, percentage of pregnant cows at 150d, and gestational loss were analyzed. No difference was observed between healthy and diseased cows in the PR at the first service or for days open. Diseased cows showed greater gestational loss and the percentage of pregnant cows at 150d postpartum was higher among healthy cows. Cows with a BCS ≥ 3.0 at prepartum had a lower PR at the first service and shorter days open. In conclusion, dairy herds affected by diseases during postpartum show impaired reproductive efficiency